Electrospun Fibers of Cyclodextrins and Poly(cyclodextrins) - Costoya, Alejandro (Molecules, 2017)
Cyclodextrins (CDs) can endow electrospun fibers with outstanding performance characteristics that rely on their ability to form inclusion complexes. The inclusion complexes can be blended with electrospinnable polymers or used themselves as main components of electrospun nanofibers. In general, the presence of CDs promotes drug release in aqueous media, but they may also play other roles such as protection of the drug against adverse agents during and after electrospinning, and retention of volatile fragrances or therapeutic agents to be slowly released to the environment. Moreover, fibers prepared with empty CDs appear particularly suitable for affinity separation. The interest for CD-containing nanofibers is exponentially increasing as the scope of applications is widening. The aim of this review is to provide an overview of the state-of-the-art on CD-containing electrospun mats. The information has been classified into three main sections: (i) fibers of mixtures of CDs and polymers, including polypseudorotaxanes and post-functionalization; (ii) fibers of polymer-free CDs; and (iii) fibers of CD-based polymers (namely, polycyclodextrins). Processing conditions and applications are analyzed, including possibilities of development of stimuli-responsive fibers.